A novel "on–off–on" fluorescence assay for the discriminative detection of Cu(ii) and l-cysteine based on red-emissive Si-CDs and cellular imaging applications. Issue 5 (8th January 2020) - Zan, Minghui; Li, Cong; Zhu, Daoming; Rao, Lang; Meng, Qian-Fang; Chen, Bei; Xie, Wei; Qie, Xingwang; Li, Li; Zeng, Xiaojiao; Li, Yirong; Dong, Wen-fei; et al.
Abstract : Copper ions (Cu 2+ ) and l- cysteine (l- Cys) in the human body always play critical roles in various physiological processes, while abnormal Cu 2+ and l- Cys concentrations in the biological system lead to many diseases. Abstract : Copper ions (Cu 2+ ) and l- cysteine (l- Cys) in the human body always play critical roles in various physiological processes, while abnormal Cu 2+ and l- Cys concentrations in the biological system lead to many diseases. In this manuscript, Si-doped carbon dots (Si-CDs) with near-infrared fluorescence were designed for the detection of Cu 2+ and l- Cys through the fluorescence "on–off–on" mode. The carbon dots exhibited not only excellent optical merits including good stability against photobleaching and high chemical stability, but also superior biological compatibility. Interestingly, due to the abundant amino groups distributed on the surface of Si-CDs, they could bind to copper ions to form cupric amine complexes and then quench the fluorescence of Si-CDs due to an electron transfer process. In addition, upon the addition of l- Cys, the FL intensity of Si-CDs could be effectively recovered accompanied with complexation between Cu 2+ and the functional groups in l- Cys, due to which Cu 2+ was removed from the surface of Si-CDs. Notably, as far as we know, these are the first red-emitting carbon dots for copper ion and l- Cys assays in water samples and human plasma samples. Furthermore, this strategy was successfully applied to the determination of Cu 2+ and l- Cys in living systems, demonstrating great practicability in biomedical applications.